2003
DOI: 10.1614/wt02-045
|View full text |Cite
|
Sign up to set email alerts
|

Purple Nutsedge Control and Potato (Solanum tuberosum) Tolerance to Sulfentrazone and Halosulfuron1

Abstract: Five field studies on sandy soils with ≤ 1% organic matter in south Texas showed that halosulfuron at 0.066 kg/ha preemergence (PRE) controlled ≥ 92% purple nutsedge and at 0.066 kg/ha postemergence (POST) controlled purple nutsedge 77 to 95%. Sulfentrazone at 0.11 to 0.28 kg/ha PRE or POST controlled purple nutsedge < 65% at one location but > 75% at two other locations. Poor control at the one location may have been due to a lack of early-season rainfall or irrigation. Potatoes were stunted 5 to 26% with hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 23 publications
4
54
0
Order By: Relevance
“…Sulfonylurea herbicides can be used for grassy weed control as soil and foliar applications (10). This class of herbicides has been studied extensively for use in agricultural crops (4,5), and has been utilized for sedge control in turf (1,8). However, many of the new chemicals have not been fully tested for safety or control of turf species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfonylurea herbicides can be used for grassy weed control as soil and foliar applications (10). This class of herbicides has been studied extensively for use in agricultural crops (4,5), and has been utilized for sedge control in turf (1,8). However, many of the new chemicals have not been fully tested for safety or control of turf species.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonylurea chemistries are an economically important class of herbicides used for weed control in agricultural crops as well as turf (2,5). The characteristics are very low use rates, excellent selectivity, and low mammalian toxicity (3).…”
Section: Introductionmentioning
confidence: 99%
“…Halosulfuron (Grichar et al, 2003;Nelson & Renner, 2002;Vencill et al, 1995), sulfentrazone (Grichar et al, 2003;Wehtje et al, 1997), and metolachlor (Cornelius et al, 1985;Obrigawitch et al, 1980) provide soil residual activity on Cyperus species with control often extending for many weeks or months after applications. While these herbicides are viable alternatives to fumigation in vegetable production, they may cause injury to newly transplanted crops (Figure 2), and potential carryover issues to subsequent crops.…”
Section: Soil Applied Herbicidesmentioning
confidence: 99%
“…The currently registered herbicides do not provide effective Cyperus spp. Control, except for halosulfuron . Tumbleson and Kommedahl reported that one Cyperus esculentus tuber produced 6900 tubers and 1900 shoots within 1 year.…”
Section: Introductionmentioning
confidence: 97%